PELATIHAN MANAJEMEN UNTUK MENINGKATKAN KEMAMPUAN PELAKU USAHA MIKRO DAN KECIL (UMK) BIDANG KULINER DI KOTA BANDUNG - Probowo Erawan Sastroredjo; Maria Merry Marianti; Paulina Permatasari; Istiharini Istiharini; Natalia Christi (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The target of this training is to increase the ability of micro and small entrepreneurs in the culinary field with the knowledge of finance, marketing, and production so that they can improve their business strategies and business management, increase sales and profits of their companies in a sustainable manner, develop and increase the size of their companies especially during COVID-19 pandemic. The training method is carried out online and offline. There are 3 stages carried out, namely: before, during, and after the training. Prior to the training, prospective participants are selected based on the criteria for the type of business and domicile that have been determined, namely in the city of Bandung. After that, training was carried out for 12 meeting sessions with varied topics covering management functions that are often applied in a company. The materials provided are Strengths Weaknesses Opportunities Threats (SWOT) Analysis and Business Model Canvas (BMC), Product Development Strategy and Digital Marketing, Brand and Copyright, Calculating Cost of Production, Making Financial Reports, Making Product Photos, Workplace Management: 5S Program, Health and Work Safety Program, Raw Material Purchase Management, Credit Management, Product Promotion Through Social Media, Product Quality Management. After the training had been completed, the trainers continued to provide regular assistance regarding the application of the knowledge that had been given during the training, as well as providing input on what Micro and Small Enterprises (MSEs) had implemented in their business.